Expired Pharmaceutical Drugs as Tribopositive Material for Triboelectric Nanogenerator (Adv. Sustainable Syst. 12/2021). (10th December 2021) - Chougale, Mahesh Y.; Saqib, Qazi Muhammad; Khan, Muhammad Umair; Shaukat, Rayyan Ali; Kim, Jungmin; Dubal, Deepak; Bae, Jinho
Abstract : Triboelectric Nanogenerators In article number 2100205, Jinho Bae and co‐workers present a unique strategy to reduce pharmaceutical pollution and address the energy crisis. Expired pharmaceutical drugs represent persistent toxic substances, but have the potential to be used as electric generator materials. The recycling of the expired drugs in the form of triboelectric nanogenerators is a promising way to sustain a clean and green environment.